Immigration detention law, history, politics - Wilsher, Daniel, 1966-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2012)
"The liberal legal ideal of protection of the individual against administrative detention without trial is embodied in the habeas corpus tradition. However, the use of detention to control immigration has gone from a wartime exception to normal practice, thus calling into question modern states' adherence to the rule of law. Daniel Wilsher traces how modern states have come to use long-term detention of immigrants without judicial control. He examines the wider emerging international human rights challenge presented by detention based upon protecting 'national sovereignty' in an age of global migration. He explores the vulnerable political status of immigrants and shows how attempts to close liberal societies can create 'unwanted persons' who are denied fundamental rights. To conclude, he proposes a set of standards to ensure that efforts to control migration, including the use of detention, conform to principles of law and uphold basic rights regardless of immigration status"--
Machine generated contents note: 1. The emergence of detention: from free movement to regulated boarders in the common law world; 2. Modern immigration detention: the growth of the bureaucratic enterprise in United States, United Kingdom, Australia and France; 3. International law and immigration detention: between territorial sovereignty and emerging human rights norms; 4. Immigration detention and the European Union: the supra-national dimension and the demise of territorial sovereignty?; 5. Immigration detention as a tool of public and national security: the problem of internment in modern times; 6. Global migration and the politics of immigration detention; 7. Drawing boundaries around detention: finding a principled and practical approach.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Illegal aliens; Detention of persons; Emigration and immigration law; Electronic books